2022
DOI: 10.1161/jaha.122.025969
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Duration, Napping, and Sleep Patterns With Risk of Cardiovascular Diseases: A Nationwide Twin Study

Abstract: Background Although sleep disorders have been linked to cardiovascular diseases (CVDs), the association between sleep characteristics and CVDs remains inconclusive. We aimed to examine the association of nighttime sleep duration, daytime napping, and sleep patterns with CVDs and explore whether genetic and early‐life environmental factors account for this association. Methods and Results In the Swedish Twin Registry, 12 268 CVD‐free twin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Age, systolic blood pressure, HDL, fasting blood sugar levels, TC, usage of anti-hypertensive medications, sedentary lifestyles, smoking, sleep deprivation, and irregular sleep patterns are vascular risk factors (8, [17][18][19], The patients were split into two groups: those with low and high vascular risk. Our study found that age, SP, TC, and GLU were increased in the high vascular risk group, which was consistent with the grouping results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, systolic blood pressure, HDL, fasting blood sugar levels, TC, usage of anti-hypertensive medications, sedentary lifestyles, smoking, sleep deprivation, and irregular sleep patterns are vascular risk factors (8, [17][18][19], The patients were split into two groups: those with low and high vascular risk. Our study found that age, SP, TC, and GLU were increased in the high vascular risk group, which was consistent with the grouping results.…”
Section: Discussionmentioning
confidence: 99%
“…Age, gender, systolic blood pressure, TC, smoking habits, HDL, usage of antihypertensive medicines, fasting blood glucose levels and sedentary lifestyles are the key vascular risk factors for the population (8). Sleep deprivation and poor sleep patterns are valuable for the screening of patients with an increased risk of CVD (17,18). Patients with less than three vascular risk factors (other than sex) were categorized as having low vascular risk, whereas those with three or more vascular risk factors (other than sex) were categorized as having high vascular risk (19).…”
Section: Grouping According To Risk Factors Of Cardiovascular Disease...mentioning
confidence: 99%
“…Inclusion criteria: Persons (1) Aged between 50 and 85 years; (2) With one or more cerebral vascular risk factors, such as hypertension, diabetes, hyperlipidemia, and smoking; (3) With typical characteristics of CSVDs in MRI scanning: WHMs (Fazekas 1 and above) are necessary, encephalography, subcortical infarction, perivascular space enlargement, and cerebral micro bleedings; (4) With symptoms involved in non-embolic lacunar stroke (unilateral motor/sensory impairment affecting at least two parts of the body (face, upper extremity, lower extremity, cognitive impairment, gait impairment, dysphagia, dysuria, and mood disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Short-time duration of sleep is associated with late-onset dementia 2 . In addition, sleep time <7 hours or >10 hours/night, napping, and poor sleep patterns are associated with an increased risk of cardiovascular disease 3 . Goldman et al found that glymphatic failure during sleep was associated with the risk of dementia, 4 and Hong et al found that hippocampal subfield atrophy in chronic insomnia was associated with impaired cognition 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Human health is closely related to sleep chronotypes 45 , which are behavioral manifestations of circadian rhythms 79 . In perspective studies, early chronotype is often regarded as a sign of healthy sleep behavior 80,81 . Individuals with an early chronotype are typically at a reduced risk of developing cardiovascular diseases 82 and heart failure 81 .…”
Section: An Atlas Of Sleep Associations With Multi-modal Brain and Ca...mentioning
confidence: 99%